THE INFLUENCE OF MOTIVATION AND COMMITMENT OF HEALTH WORKERS ON LACTATION MANAGEMENT SERVICES AT RSIA ASIH BALIKPAPAN - Meriah Yacobi; Cri Sajjana Prajna Wekadigunawan; Muhammad Reza Hilmy (International Journal Labs, 2022)
Mothers and children are family members who need to get priority in the implementation of health efforts, because mothers and children are a vulnerable group. This is related to the phase of pregnancy, childbirth and postpartum in the mother and the phase of growth and development in children. The importance of maternal and child health efforts is one of the priorities for health development in Indonesia. Maternal Mortality Rate (MMR), Neonatal Mortality Rate (AKN), Infant Mortality Rate (IMR) and Toddler Mortality Rate (AKABA) are some indicators to see the success of health development in the community. Objective: To analyze the effect of motivation and commitment of health workers on lactation management services at RSIA Asih Balikpapan Research method: this research is an associative quantitative research with hypothesis testing to see the effect between variables. The research method used a path analysis research model which was conducted on 80 respondents. Research Results: The results showed that motivation and commitment had a significant effect on lactation management services with a P value = 0.00..